ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN MUSI RAWAS - Fitri, Annisa; Triharyati, Eri; Mulyono, Hardi (Politeknik Ganesha Medan, 2024)
The problem examined in this study is about the Financial Performance of the Culture and Tourism Office of Musi Rawas Regency in terms of Eifficiency, Eiffectiveness and Harmony Ratios. This study uses a qualitative method. Data collection techniques used are observation, interviews and documentation. The results showed that the Financial Performance of the Culture and Tourism Office of Musi Rawas Regency in terms of Efficiency Ratio, from 2017 to 2022 can be categorized as inefficient with an aveirange efficiency ratio valuei of 93,6%. The Financial Performance of the Musi Rawas Regency Culture and Tourism Office in terms of the Effectiveness Ratio, from 2017 – 2022 as a whole is in the effective criteria with an average effectiveness ratio valuei of 94%. Thei Financial Performance of the Office of Culture and Tourism of Musi Rawas Regency in terms of the Conformity Ratio, from 2017 – 2022 can be said to be compatible, with an average compatibility ratio value of 77,3%. The results of this research are expected to be useful for the Culture and Tourism Office of Musi Rawas Regency. They need to pay more attention to things that can be a potential source of income, such as paying special attention to tourist objects.